Shifting as a Therapeutic Experience during the Covid-19 Pandemic - Sánchez Vásquez, Elizabeth (2025)
This article explores the practice of shifting as a therapeutic method popularized by adolescent women in Mexico during the COVID-19 pandemic. Emerged as a ritual on TikTok and drawed from popular media culture (Possamai, 2010), shifting quickly formed a solid virtual community among young people seeking an escape from pandemic uncertainty. A hypothesis, derived from two years of virtual fieldwork, suggests that youth, in their search for emotional support on digital social networks, found a space for self-expression, containment , and belonging within shifting and its community. For the analysis, digital netnography was employed. This involved constructing a stakeholder map to identify key community actors, followed by 15 semi-structured interviews and 5 in-depth interviews. The research classifies shifting as a cathartic ritual aimed at alleviating emotional tensions in the face of the Social Drama (Turner, 1975) caused by the pandemic.    [MA1]¿Esto se refiere a apoyo emocional?